Reliability of noninvasive assessment of systolic pulmonary artery pressure by Doppler echocardiography compared to right heart catheterization: analysis in a large patient population - Greiner, Sebastian; Jud, Andreas; Aurich, Matthias; Heß, Alexander; Hilbel, Thomas; Hardt, Stefan; Katus, Hugo; Mereles, Derliz (Journal of the American Heart Association, 2014)
BackgroundPulmonary artery pressure (PAP) is an important marker in cardiovascular disorders, being closely associated with morbidity and mortality. Noninvasive assessment by Doppler echocardiography is recommended by current guidelines. So far, the reliability of this method has been assessed only in small studies with contradictory results. Therefore, the aim of this study was to analyze the reliability of noninvasive PAP assessment by Doppler echocardiography compared to invasive measurements in a large patient population.Methods and ResultsWe retrospectively analyzed data from a large tertiary cardiology department over 6 years in order to compare invasively measured PAP to estimated PAP from echocardiography examinations. N=15 516 patients fulfilled inclusion criteria and n=1695 patients with timely matched examinations (within 5 days) were analyzed. In n=1221 (72%) patients, pulmonary hypertension (PH) was diagnosed invasively (postcapillary PH: n=1122 [66%]; precapillary PH: n=99 [6%]). Systolic pulmonary artery pressure (sPAP) was 45.3±15.5 mm Hg by Doppler echocardiography and 47.4±16.4 mm Hg by right heart catheterization. Pearson's correlation coefficient was r=0.87 (P<0.0001). Mean right atrial pressure (RAP) was 12.0±5.7 mm Hg by right heart catheterization and was estimated to be 12.1±6.6 mm Hg by echocardiography (r=0.82, P<0.0001). Bland-Altman analysis showed a bias of −2.0 mm Hg for sPAP (95% limits of agreement −18.1 to +14.1 mm Hg) and +1.0 mm Hg for RAP (95% limits of agreement +0.1 to +1.9 mm Hg). Noninvasive diagnosis of pulmonary hypertension with Doppler echocardiography had a good sensitivity (87%) and specificity (79%), positive and negative predictive values (91% and 70%), as well as accuracy (85%) for a sPAP cut‐off value of 36 mm Hg (AUC 0.91, P<0.001, CI 0.90 to 0.93).ConclusionsIn this study, Doppler echocardiography proved to be a reliable method for the assessment of sPAP, being well suited to establish the noninvasive diagnosis of pulmonary hypertension in patients with cardiac diseases.